Visi Kolonial dan Mimpi Kosmopolitan: Representasi Indonesia dan Thailand dalam Catatan Perjalanan Barat Kontemporer - Akmal, Ramayda (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article investigates the representation of Indonesia and Thailand in contemporary Western travel writing, focusing primarily on how this cultural production presents the two countries temporally and spatially. Furthermore, it elaborates the rhetorics of colonial legacy and cosmopolitan vision within the representation process. To solve its research problems, this study applies several concepts, including the concept of travel writing, the concept of subjectivity, the concept of colonial legacy, and the concept of cosmopolitan vision. This research is carried out methodologically through a hermeneutic reading of the studied works by also considering the external factors that influence them. For this research, a sample of three works of western travel writing published in the past few decades and written by western travel writers from variety of backgrounds, were selected. They are Paul Theroux's The Great Railway Bazaar (1976); Pico Iyer's Video of Night at Kathmandu (1988); and Robert Kaplan's Monsoon, The Indian Ocean and the Future of American Power (2010). This study finds that Indonesia and Thailand have been represented diversely in contemporary western travel writing, creating discourses that are influenced by colonial legacy or cosmopolitan vision.